Vaccination with Delta-PGM in the control of buffalo (Bubalus bubalis) brucellosis - Alfredo Sánchez-Villalobos; Leandro Salas; Hengelbert Fuenmayor; Omaira Contreras; Enmanuel Machado (Revista Científica)
Brucellosis in buffalos represents an unresolved problem for consolidating the species in Venezuela. In 2020, a control program started in 5 associated farms with an estimated ˃ 20% prevalence. The program focused on: vaccination with Delta-PGM (Agropharma Laboratories, Buenos Aires, Argentina), 2ml subcutaneous injection in 3- to- 8- month females, aiming to secure two dosages before the service (2nd dosage seven months after the first), and detection/elimination of the infected through serial diagnosis with buffered plate antigen test (BPA, Agropharma Laboratories, Buenos Aires, Argentina) and fluorescence polarization assay (FPA, Biotehnika Laboratories, Serbia). The objectives included showing the vaccine’s pro-tection capacity against the disease in natural conditions with important naturally occurring challenges (prevalence ˃ 20%) and differentiating infected from vaccinated animals (DIVA) with the previously described diagnostic test. In October 2022, diagnostic evaluation was carried out in 1,340 replacement females from this system, vaccinated or not, and divided into four groups according to body weight (G1: less than 170 k; G2: between 171 and 220; G3: from 221 to 270; G4: above 270 k). The data were analyzed through Friedman’s non-parametric statistical test, allowing comparisons between the observed characters. Ninety animals (90) without vaccination were detected, belonging to groups G1 and G2, one being positive for brucellosis (1/90; 1.11%; p>0.05). Of the total evaluated population, 47 were reactive to BPA (47/1340; 3.5%), and only 16 were confirmed positive for brucellosis with FPA (16/1340; 1.2%; p<0.05). Of them, 8 (50%) belonged to G2 and another 8 (50%) to G3, without detection in G1 or G4, showing statistical differences (p<0.05). Regarding the vaccination and positivity correlation, it is noteworthy that 14 (14/1160; 1.20%) of the positives for brucellosis had received primary vaccination and a booster; none with two boosters was identified as positive (p<0.05). On the other hand, it stands out that three positives had a history, as they came from mothers reported to be reactive to BPA. Concerning the origin of the positives, the majority (68.8%) belonged to two problem farms (p<0.05). In conclusion, under the studied conditions, a high efficiency of the established control model was verified, which was associated with the protective capacity of the Delta- PGM strain vaccine. Using two applications prior to service, this model resulted in a significant reduction of infections in relation to their dams (p<0.05). It also showed that Delta-PGM allows differentiation between infected, vaccinated, and healthy animals (DIVA); therefore, its use does not lead to any diagnostic confusion when using BPA and/or FPA.